Pampedia (Educación Universal) - Gladys Mary Teive Auras (Revista Brasileira de História da Educação, 2012)
COMENIUS, Juan Amós. Pampedia (Educación Universal). Trad. Federico Gómez R. de Castro. Madrid: UNED, 1992.